Thermal Energy Storage for Medium and High Temperatures Concepts and Applications - Steinmann, Wolf-Dieter (Wiesbaden Springer Fachmedien Wiesbaden, 2022)
Energy storage is considered an essential component for ensuring security of supply in future energy systems with increasing shares of renewable energies. Since thermal energy accounts for a significant portion of the total demand, the use of thermal storage systems is an obvious choice. This book focuses on systems operating between 100–1200 °C and is intended as a resource to provide the necessary information for understanding, selecting, developing, operating, and managing these storage systems. In the first part an overview of state of the art and innovative storage concepts is given, describing their characteristics and providing the fundamentals required for the design of these storage systems. Various areas of application for thermal storage systems are described in the second part of this book, demonstrating the selection of a storage concept and its adaptation to the specific boundary conditions. One example for these applications areas are commercial solar thermal power plants, where the cumulative integrated storage capacity allows the off-sun generation of electricity in the multi-GWh range. The book also includes emerging application areas like the facility scale storage of electric energy or industrial application where thermal storage can improve the energy efficiency of batch processes or allows the demand-side management of renewable energy. After the master in Aerospace Engineering Wolf-Dieter Steinmann received his PhD in Energy Engineering from Stuttgart University. For more than 20 years he has been working as a project manager at the German Aerospace Center (DLR) in numerous national and international projects dealing with thermal storage technology, from fundamental research to pilot-scale demonstration. He is author or co-author of more than 100 publications and holds more than 20 patents on the subject
Basics -- Thermal energy storage as option to improve energy efficiency -- Evaluation criteria -- Classification of concepts -- Fundamental storage concepts -- Sensible heat energy storage -- Latent heat energy storage -- Thermochemical energy storage -- Applications -- Power Plants -- Process Industry -- Storage of electricity -- Vehicles
Keywords: Mechanical and Thermal Energy Storage; Energy storage; Bioremediation; Biotechnology; Environmental Engineering/Biotechnology; Energy policy; Energy Policy, Economics and Management; Environmental engineering; Energy and state